Global Trends of "Green" Economy Development as a Factor for Improvement of Economical and Social Prosperity; Procedia - Social and Behavioral Sciences; Vol. 166 : Proceedings of The International Conference on Research Paradigms Transformation in Social Sciences 2014 (RPTSS-2014), 16–18 October 2014, Tomsk, Russia - Egorova M. S. Mariya Sergeevna (2015, 2015)
Title screen